Distinction between Pneumothorax and Pneumomediastinum Using Point of Care Ultrasound (POCUS): Role of Still Lung Point - Sagaser, Anna E.; Reeves, Ashley; Arnautovic, Tamara; Sanchez-Esteban, Juan (American Journal of Perinatology Reports, 2024)
The rapid identification and management of air leak syndrome in the neonatal intensive care unit is critical to prevent and/or minimize short- and long-term complications. Traditionally, chest X-ray is used to diagnose pneumothorax or pneumomediastinum. However, point-of-care ultrasound is increasingly being used for procedural and diagnostic purposes. Current ultrasound guidelines recommend specific criteria to diagnose pneumothorax in newborns including sharp A-lines, absence of B-lines, lack of shimmering of the pleural line, and the presence of a lung point. Pneumomediastinum may have similar ultrasound characteristics. In this case report, we present two cases of pneumomediastinum in newborns, describe the associated ultrasound findings, and review some of the criteria to differentiate from pneumothorax, including the presence of a still lung point. A high index of suspicion for pneumomediastinum should be maintained when using ultrasound to diagnose air leak given the overlapping sonographic features with pneumothorax. This distinction is of particular importance if evacuation of air by needle thoracentesis or the placement of a chest tube is under consideration.
Keywords: POCUS; pneumothorax; pneumomediastinum; lung sliding; ultrasound; air leak syndrome; newborn; lung point